Cryoablation: an Alternative in the Treatment of Breast Cancer - Elvia Paucar Cepeda; Mario David Pinta Riofrio; Catalina del Rosario Boada Zurita (Revista Finlay)
Cryoablation is a cryotherapy treatment for tumors located in the lungs, mediastinum, bones, liver, kidney, prostate, and breast. It can be curative or palliative and is effectively developed in modern medicine. It seeks to mitigate the fifth cause of death worldwide, breast cancer. The present investigation is a bibliographic review about percutaneous cryoablation as a safe method that does not involve other organs close to the part to be intervened. It is an outpatient procedure, with guided image, minimal invasion, local anesthesia and immediate recovery. The results show that it is recommended in elderly patients or those who are at high risk for surgery due to their disease and for any patient with the aforementioned condition. The objective of the study is to theoretically support the benefits of cryotherapy, measure and test its efficacy, as well as its tolerance in the long and medium term.